The Influence of Demographics, Financial Literacy, and Social Media on Online Loan Users (Fintech Lending) in Medan City - Duhusokhi Laia; Afriza Amir; Nur Ahmadi Bi Rahmani (SEAN Institute, 2026)
This study investigates the influence of demographics, financial literacy, and social media on online loan users or fintech lending users in Medan City. The growing use of online loan services indicates that digital financial platforms have become an alternative source of financing for the public due to their accessibility, fast process, and flexibility. This research applies a quantitative approach with a causal associative method. Data were collected through questionnaires distributed to 60 respondents who had used or were currently using online loan services in Medan City, including students, employees/professionals, and freelancers. The data were analyzed using multiple linear regression with SPSS. The findings reveal that, partially, demographic factors and social media have a positive and significant effect on the use of online loans, while financial literacy does not have a significant effect. Simultaneously, demographics, financial literacy, and social media significantly influence the use of online loans. These findings indicate a behavioral gap, in which the use of online loans is more strongly driven by individual characteristics and exposure to digital information than by financial understanding.